2000
DOI: 10.1097/00005053-200007000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Trauma Related Symptoms of Bosnian Refugees Who Have not Sought Mental Health Services

Abstract: The objective of this study was to profile trauma related psychiatric symptoms in a group of refugees not seeking mental health services and to consider the services implications. The study involved research assessments of two groups of Bosnian refugees: those who have not presented for mental health services and those who have. A total of 28 of 41 nonpresenters (70%) met symptom criteria for posttraumatic stress disorder (PTSD) diagnosis. All service presenters (N = 29) met symptom criteria for PTSD diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 11 publications
3
49
1
Order By: Relevance
“…Specifically, and not surprisingly, health problems were related to prospective medical care use, consistent with two previous studies of Vietnam veterans inquiring about (albeit, previous) medical care use [Marshall et al, 1997[Marshall et al, , 1998]. However, health status did not mediate the relationship between lifetime MH treatment use and prospective health care use, which is inconsistent with a study of combat veterans [Solomon, 1989] and another with refugees [Weine et al, 2000], both of which found relations between previous MH care use and current health status. Thus, from these studies we may only suggest that among trauma survivors health problems are related to medical care use.…”
Section: Discussionsupporting
confidence: 39%
See 2 more Smart Citations
“…Specifically, and not surprisingly, health problems were related to prospective medical care use, consistent with two previous studies of Vietnam veterans inquiring about (albeit, previous) medical care use [Marshall et al, 1997[Marshall et al, , 1998]. However, health status did not mediate the relationship between lifetime MH treatment use and prospective health care use, which is inconsistent with a study of combat veterans [Solomon, 1989] and another with refugees [Weine et al, 2000], both of which found relations between previous MH care use and current health status. Thus, from these studies we may only suggest that among trauma survivors health problems are related to medical care use.…”
Section: Discussionsupporting
confidence: 39%
“…Specifically, studies demonstrate that a PTSD diagnosis predicts a greater likelihood (and intensity) of MH [Boscarino et al, 2002;New and Berliner, 2000;Zhang et al, 2004] and medical services [Fagan et al, 2003;Zhang et al, 2004]. Three investigations also reveal that PTSD severity increases the likelihood of MH care use [Calhoun et al, 2002;Goto et al, 2002;Weine et al, 2000], whereas two studies fail to support this finding [Elhai et al, 2004;Schwarz and Kowalski, 1992].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low or 'lower than expected' levels of service use may in part reflect reduced levels of need for service and a great degree of resilience (e.g. (Siriwardhana et al, 2014;Steel, Silove, Chey, Bauman, & Phan, 2005;Weine et al, 2000)). Nevertheless, studies that have measured mental health needs and service utilisation levels have found that the majority of young refugees who have significant mental health needs do not access services (e.g., (Bean, Eurelings-Bontekoe, Mooijaart, & Spinhoven, 2006;Ziaian, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Given the Bosnian refugees' strong personality and emotional independence, it is likely that they can underestimate their own emotional and mental health needs in the aftermath of a disaster. Previous literature has repeatedly demonstrated the severity of mental health outcomes, including PTSD, major depression, and major anxiety, among Bosnian refugees after the Bosnian war [36][37][38], and this should be closely considered in the wake of above findings.…”
Section: Discussionmentioning
confidence: 78%